New aspects of pathogenesis of respiratory dysfunction in case of chronic rheumatic heart disease - G. S. Taktashov (Zaporožskij Medicinskij Žurnal)
Aim. Pathogenesis of respiratory dysfunction and hemorheology in case of chronic rheumatic heart disease is to be defined.